RELIGION AND INTERCULTURAL COMMUNICATION: THE IMPACT OF RELIGIOUS BELIEFS ON COMMUNICATION PRACTICES - Qo‘shatova Gulbadan (TADQIQOTLAR, 2025)
Abstract: Religion profoundly shapes individuals’ worldviews, moral frameworks, and communication practices. Across diverse cultures, religious beliefs influence verbal and nonverbal interaction, conflict resolution, ethical norms, and social behavior. This paper explores the impact of religious ideology on intercultural communication, highlighting mechanisms through which faith informs communication practices, including verbal choice, gesture, tone, and nonverbal cues. Using qualitative methods, including literature review, case studies, and thematic analysis, the study demonstrates that awareness of religious norms improves intercultural understanding, reduces misunderstandings, and fosters ethical dialogue. Conversely, ignoring these norms can result in social friction, miscommunication, and ethical dilemmas.